Numerical and Field Investigations on Rockburst Risk Adjacent to Irregular Coal Pillars and Fault - Zhi-long He; Cai-ping Lu; Xiu-feng Zhang; Chao Wang; Bao-qi Wang; Tao Zhou (Shock and Vibration)
Irregular coal pillars are often reserved in the upper coal seam in multiseam mining due to the limitation of geological conditions and mining methods. Diffused and transmitted stress in the pillars will form the stress concentrated areas in the lower coal seam and will increase the risk of rockburst. Based on the upper irregular pillars and fault encountered in the 7301 working face of the Zhaolou coal mine, this paper studies the evolution of stress and energy when the working face passed through the area affected by pillars. The adopted methods include numerical simulations and field monitoring. The change in stress concentration factor and stress gradient because of the mining activities in lower coal seam was analyzed by numerical simulation, indicating that the stress gradient reaches a peak when the working face is closed to the area under the edge and junction of pillars, which has the high risk of inducing rockburst. The sources’ location, variation rule of microseismic (MS) total energy and events, frequency spectrum distributions, and source parameters are discussed, respectively, based on the field monitoring data. The main conclusions were obtained as follows: (1) The total energy and event counts reach the peak when working face is close to the area under the edge and the junction of pillars. (2) The dominant frequency transfers from high frequency to low frequency, the stress drop reaches the peak value, the energy index decreases sharply, and the cumulative apparent volume increases sharply, which all are obvious precursory characteristics before rockburst.